Effect of Stereochemistry of Avermectin‐Like 6, 6‐Spiroketals on Biological Activities and Endogenous Biotransformations in Streptomyces avermectinius. Issue 5 (26th February 2014) - Sun, Peng; Zhao, Qunfei; Zhang, Hua; Wu, Jiequn; Liu, Wen
Abstract Natural avermectins (AVEs) share a 6, 6‐spiroketal moiety with an exclusive R configuration at the C21 spirocyclic junction. Herein, we report the characterization of nine AVE‐like spiroketals of two types (C21 S and R) in a mutant strain that lacks spirocyclase activity. Comparative analysis of their structures facilitated evaluation of the effect of stereochemistry on endogenous biotransformations and biological activities of the spiroketals.